Restricting child-directed ads is effective, but adding a time-based ban is better: evaluating a multi-phase regulation to protect children from unhealthy food marketing on television - Francesca R. Dillman Carpentier; Fernanda Mediano Stoltze; Marcela Reyes; Lindsey Smith Taillie; Camila Corvalán; Teresa Correa (BMC, 2023)
Abstract Background As childhood obesity rates continue to rise, health organizations have called for regulations that protect children from exposure to unhealthy food marketing. In this study, we evaluate the impact of child-based versus time-based restrictions of "high-in" food and beverage advertising in Chile, which first restricted the placement of "high-in" advertisements (ads) in television attracting children and the use of child-directed content in high-in ads and, second, banned high-in ads from 6am-10pm. "High-in" refers to products above regulation-defined thresholds in energy, saturated fats, sugars, and/or sodium. High-in advertising prevalence and children's exposure to high-in advertising are assessed. Methods We analyzed a random stratified sample of advertising from two constructed weeks of television at pre-regulation (2016), after Phase 1 child-based advertising restrictions (2017, 2018), and after the Phase 2 addition of a 6am-10pm high-in advertising ban (2019). High-in ad prevalence in post-regulation years were compared to prior years to assess changes in prevalence. We also analyzed television ratings data for the 4-12 year-old child audience to estimate children's ad exposure. Results Compared to pre-regulation, high-in ads decreased after Phase 1 (2017) by 42% across television (41% between 6am-10pm, 44% from 10pm-12am) and 29% in programs attracting children (P < 0.01). High-in ads further decreased after Phase 2, reaching a 64% drop from pre-regulation across television (66% between 6am-10pm, 56% from 10pm-12am) and a 77% drop in programs attracting children (P < 0.01). High-in ads with child-directed ad content also dropped across television in Phase 1 (by 41%) and Phase 2 (by 67%), compared to pre-regulation (P < 0.01). Except for high-in ads from 10pm-12am, decreases in high-in ads between Phase 1 (2018) and Phase 2 were significant (P < 0.01). Children's high-in ad exposure decreased by 57% after Phase 1 and by 73% after Phase 2 (P < 0.001), compared to pre-regulation. Conclusions Chile's regulation most effectively reduced children's exposure to unhealthy food marketing with combined child-based and time-based restrictions. Challenges remain with compliance and limits in the regulation, as high-in ads were not eliminated from television. Yet, having a 6am-10pm ban is clearly critical for maximizing the design and implementation of policies that protect children from unhealthy food marketing.